Studies on the Gonadosomatic Index and Fecundity of Mystus gulio (Ham.) (Progressive Agriculture, 2013)
The study was conducted for a period of twelve months from January to December 2006 to determine the gonadosomatic index (GSI) and fecundity of Mystus gulio. Total 370 of Mystus gulio were examined during the study period. The sex ratio (male:female) of the investigated fish was 1:1.22 and generally female was larger than male. The fish was found to have a wide spawning season (March to November) with a single spawning peak in July as indicated by the gonadosomatic index and ova diameter. Fecundity of the fish was ranged from 3,891 to 1,68,358 with an average of 32,909.49 during the period of study and was found to increase with the increase of body length and weight. The relationships between fecundity and total-length, body-weight, gonad-length and gonad-weight were found linear and statistically highly significant (p